Evaluating the Social Responsibility Program by PT. Petrokimia Gresik - Titiek Irewati (Indonesian Journal of Multidisciplinary Science, 2023)
State-owned companies have an obligation to carry out Corporate Social Responsibility (CSR) activities in a unified and sustainable manner, not only in the form of temporary events that are charitable in nature. Qualitative research with case study method were used to determine the effectiveness of the implementation of the Social Responsibility program by PT. Petrokimia Gresik. Based on the tracing of documents and survey facts, it is known that the implementation of CSR by companies with a direction to advance food security so that it has a heavy point in the agricultural sector at large. The principle of partnership funds with a system of groups and cooperatives while Community Development for village villages that are in the ring one with the company directs to the field of education and skills. The response of fostered partners and followers of educational programs is relatively good because it fosters opportunities to make efforts, the ability of partners to develop technologies, systems and products. Corporate Social Performance has a positive relationship with Corporate Finance Performance with the many recognitions and awards received by PT. Petrokimia Gresik.